2018
DOI: 10.1111/petr.13169
|View full text |Cite
|
Sign up to set email alerts
|

Association of post‐transplant donor‐specific HLA antibody with liver graft fibrosis during long‐term follow‐up after pediatric liver transplantation

Abstract: The aim of this study was to evaluate the significance of post-transplant DSA as a predictor of liver fibrosis during long-term follow-up after pediatric LT. We evaluated the histological findings in 18 LT recipients who underwent liver biopsy after DSA screening. Liver fibrosis was scored based on the METAVIR fibrosis staging. Patients were divided into 2 groups based on histological findings, and clinical characteristics among patients with liver fibrosis were assessed. Of 18 patients, 7 were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…[32] and Tokodai et al . [33], who reported that inflammation and fibrosis in paediatric liver transplant biopsies, which are considered as morphological features of chronic rejection, were related to the presence of circulating de novo DSA, especially DSA to HLA Class II antigens. It can be speculated about the reason why non‐DSA to HLA Class II antigens in our study predicted an increased risk for the development of chronic AMR.…”
Section: Discussionmentioning
confidence: 99%
“…[32] and Tokodai et al . [33], who reported that inflammation and fibrosis in paediatric liver transplant biopsies, which are considered as morphological features of chronic rejection, were related to the presence of circulating de novo DSA, especially DSA to HLA Class II antigens. It can be speculated about the reason why non‐DSA to HLA Class II antigens in our study predicted an increased risk for the development of chronic AMR.…”
Section: Discussionmentioning
confidence: 99%
“…40 In pediatric patients an association between antibodymediated AR and progress of graft fibrosis leading to liver graft damage after LT was reported. 41,42 Furthermore, development and severity grade of liver fibrosis after LT is discussed as a potential predictor for death and graft loss in recipients. 43 The chronically inflamed environment may promote carcinogenesis and may contribute to the increased frequency of tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…41 Possible antibody-mediated graft dysfunction is being increasingly identified with HLA donor-specific antibody measurement. 42 Other well-known complications include renal dysfunction and risks of malignancy and/or post-transplant lymphoproliferative disease. Neurodevelopmental and quality of life issues are also being addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Protocol biopsies have revealed chronic graft dysfunction, even with normal liver function tests, 40 but also children with normal biopsies who might be considered for complete immunosuppression withdrawal 41 . Possible antibody‐mediated graft dysfunction is being increasingly identified with HLA donor‐specific antibody measurement 42 . Other well‐known complications include renal dysfunction and risks of malignancy and/or post‐transplant lymphoproliferative disease.…”
Section: Discussionmentioning
confidence: 99%